Carbon Molecular Sieves: Reconstruction of Atomistic Structural Models with Experimental Constraints - Kowalczyk, Poitr; Terzyk, A.; Gauden, P.; Furmaniak, S.; Wisniewski, M.; Burian, A.; Hawalek, L.; Kaneko, K.; Neimark, A. (American Chemical Society, 2014)
We propose a novel methodology for developing experimentally informed structural models of disordered carbon molecular sieves. The hybrid reverse Monte Carlo simulation method coupled with wide-angle X-ray scattering experiments is used for constructing an atomistic level model of a representative sample of carbon molecular sieve film (CMS-F) synthesized in our laboratory. We found that CMS-F possesses a disordered matrix enriched with bended carbon chains and various carbon clusters as opposed to the turbostratic carbon or graphite-like microcrystals. The porestructure of CMS-F has a defected lamellar morphology of one-dimensional periodicity with narrow (~0.4 nm) micropores. The model is applied to study adsorption properties of CMS-F with respect to adsorbates of practical interest, such as N2, H2, CO, and C6H6. Special attention is paid to the hasetransformations in the course of adsorption. In particular, we show theoretically and confirm experimentally that nitrogen solidifies within CMS-F pores at 77 K upon adsorption of 5 mmol/g, and its further adsorption is associated with the adsorbed phase compression induced by strong surface forces.